Morocco's Africa Policy - Abourabi, Yousra (Leiden Studies in Islam and Society, 2024)
Since the advent of the reign of Mohammed VI in 1999, Morocco has deployed a new continental foreign policy. The Kingdom aspires to be recognized as an emerging African power in its identity as well as in its space of projection. In order to meet these ambitions, the diplomatic apparatus is developing and modernizing, while a singular role identity is emerging around the notion of the "golden mean". This study presents, on an empirical level, the conditions of the elaboration and conduct of this Africa policy, and analyzes, on a theoretical level, the evolution of the Moroccan role identity in the international system.